2023
DOI: 10.1038/s41539-023-00192-9
|View full text |Cite
|
Sign up to set email alerts
|

Children perpetuate competence-based inequality when they help peers

Jellie Sierksma

Abstract: Exchanges of help between children are common and often have positive consequences. But not all help is equally beneficial, for example because some help does not provide an opportunity to practice and develop skills. Here I examine whether young children might perpetuate competence-based inequality by providing incompetent peers with less opportunity to practice and improve their skills compared to competent peers. Study 1 (N = 253, 6–9 years) shows that young children understand not all help is equally benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 107 publications
0
2
0
Order By: Relevance
“…Yet, even in classrooms, children might be treated differently based on their SES. Three studies in our collection—Renoux et al 12 , Schoneveld and Brummelman 13 , and Sierksma 14 —address this possibility. They demonstrate that children from low-SES backgrounds may face unequal treatment in the classroom, often at the hands of well-intentioned teachers or peers, with serious repercussions.…”
Section: Experiences That Contribute To Achievement Inequalitymentioning
confidence: 97%
See 1 more Smart Citation
“…Yet, even in classrooms, children might be treated differently based on their SES. Three studies in our collection—Renoux et al 12 , Schoneveld and Brummelman 13 , and Sierksma 14 —address this possibility. They demonstrate that children from low-SES backgrounds may face unequal treatment in the classroom, often at the hands of well-intentioned teachers or peers, with serious repercussions.…”
Section: Experiences That Contribute To Achievement Inequalitymentioning
confidence: 97%
“…Third, once children are stereotyped as being less smart, they may be treated by classmates in ways that perpetuate their presumed lack of smartness. Integrating theories from social and developmental psychology, Sierksma 14 demonstrated that children might perpetuate competence-based inequality by offering disempowering help (i.e., help that does not offer recipients an opportunity to practice and improve their skills, such as providing the right answer rather than a hint). In two preregistered experiments, children were introduced to two peers whom they later overheard were either good or not so good at a task.…”
Section: Experiences That Contribute To Achievement Inequalitymentioning
confidence: 99%